Endothelial cell damage following sulfur mustard exposure in rabbits and its association with the delayed-onset ocular lesions. (June 2013) - Kadar, Tamar; Cohen, Maayan; Cohen, Liat; Fishbine, Eliezer; Sahar, Rita; Brandeis, Rachel; Dachir, Shlomit; Amir, Adina
<x xml:space="preserve">Abstract</x> Objective: Ocular injuries following exposure to the toxic agent sulfur mustard (SM) are characterized by acute corneal erosions and inflammation of the anterior segment that may be followed by delayed corneal injuries, expressed clinically by neovascularization and epithelial defects. The present study aimed to investigate the effects of SM on corneal endothelium (CE) during the acute and delayed phase in relation to the development of the long-term pathology. Methods: Rabbit eyes were exposed to SM vapor. A clinical follow-up including pachymetry for measurement of corneal thickness were conducted up to 3 months following exposure. In vivo analysis of corneal endothelium in the central and peripheral cornea was carried out, using a contact specular microscopy. orphometric analysis of cell area and number of cells was performed, to include the acute and delayed phases. Eyes were taken for histology at different time points following exposure (1 h to 3 months). TUNEL staining (Terminal deoxynucleotidyl transferase dUTP nick end labeling) was conducted for detection of apoptosis during the acute phase. Results: SM induced acute corneal erosions and prolonged anterior segment inflammation. Corneal thickness increased within hours, declined after few days but remained higher compared to baseline value for months after the exposure, indicating a chronic edema. Apoptotic alterations were first observed at 6 h resulting in a significant decline in the number of endothelial cells at 24–48 h following exposure. Healing of the endothelium was relatively fast and at one week the Descemet's membrane was resurfaced, yet, the density and morphology of the cells was often abnormal. Moreover, histological evaluation revealed deformation and enlargement of many cells (polymegathism and pleomorphism), thickening and double layered Descemet's membrane. These changes were more pronounced in corneas displaying delayed pathology. Discussion and conclusions: SM induced apoptotic cell death of endothelial cells that was accompanied by corneal edema. The impaired healing of the endothelium, including the decrease in endothelial cell density was associated with the delayed-onset injuries. Since human corneal endothelium is almost amitotic, endothelium toxicity should be taken into consideration when testing potential treatments against ocular injuries following SM exposure.